RELATIONSHIP BETWEEN INDIVIDUALISTIC VALUES AND OPTIMISM: A STUDY OF THE MILLENNIAL GENERATION IN BULGARIA - Karaivanova, Maria (Journal of Education Culture and Society, 2020)
Aim. A quantitative study on generational differences showed a decrease in optimism among the young generation (Karaivanova, 2016). The present work aims to study in detail the relationship between individualistic values, self-esteem, and optimism among the Millennial generation. Optimism is a general expectation for positive results and positive events in life (Radoslavova & Velichkov, 2005).Method. A sample of 204 respondents from 20 to 35 years old voluntarily filled in a survey containing scales measuring individualistic values, self-esteem, and optimism. The relationship between these variables was tested using regression and mediation analyses. The results were processed using the statistical software SPSS, version 22.0.0.0, and the lavaan application in R Studio.Results. The theoretical model created and tested in this study proved to have good explanatory power for the dependent variable optimism explaining one-third of its variance and gives significant clarity on the relationship between individualistic values, self-esteem, and optimism for the young generation in Bulgaria.Conclusion. Individualistic values turned out to predict self-esteem. The more individualistic a person is, the higher they perceive their competences and social image. At the same time, being individualistic, i.e. being open for change and following one’s own interests does not make young people look more optimistically towards the future and believe in the solution of every problem they encounter. Individualistic values have a positive mediated effect on optimism with self-esteem as a mediator. Having strong self-confidence makes young people have positive expectations for the future.